2011
DOI: 10.1007/s00192-011-1481-5
|View full text |Cite
|
Sign up to set email alerts
|

Monoprosthesis for anterior vaginal prolapse and stress urinary incontinence: midterm results of an international multicentre prospective study

Abstract: Monoprosthesis with combined prepubic and transobturator arms presented high success rates for AVP repair and simultaneous SUI treatment. It has also been shown to be safe and appears to preserve sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…The Mesh group showed better anatomical improvement of AVWP in relation to the Control group. Differently to the referred review, we have observed that both groups showed a significant improvement of the vaginal symptoms and QoL impact, what is in accordance to the results presented by Palma et al These authors evaluated 104 women treated with NAZCA TC in an international multicentric study (11). Another trial with similar outcomes was published by Nguyen and Burchette (18).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The Mesh group showed better anatomical improvement of AVWP in relation to the Control group. Differently to the referred review, we have observed that both groups showed a significant improvement of the vaginal symptoms and QoL impact, what is in accordance to the results presented by Palma et al These authors evaluated 104 women treated with NAZCA TC in an international multicentric study (11). Another trial with similar outcomes was published by Nguyen and Burchette (18).…”
Section: Discussionsupporting
confidence: 90%
“…It has been described outcomes of different available meshes in the market, presented as kits (6,11) or in a standard size and molded according to surgeon's preference during surgery (12,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…journals.viamedica.pl/ginekologia_polska dure or not. While occult incontinence may coexist in up to 30% of women with POP, about 40-50% of women with POP observe a significant SUI [12,13]. NAZCA-TC is a mesh with four arms: two pre-pubic and two transobturator.…”
Section: Introductionmentioning
confidence: 99%
“…NAZCA-TC is a mesh with four arms: two pre-pubic and two transobturator. It was invented to treat anterior vaginal wall prolapse alone or together with SUI [12].…”
Section: Introductionmentioning
confidence: 99%